Amelia Bedelia goes wild! - Parish, Herman; Avril, Lynne, 1951- (New York, NY : Greenwillow Books, an imprint of HarperCollins Publishers, 2014)
"Amelia Bedelia is sick the day her class goes to visit the zoo. She doesn't want to be left out, so she comes up with a brilliant idea--she'll create a zoo in her backyard, using all her classmates' pets. But she doesn't know exactly how to tell her parents about her great plan"--Provided by publisher.
2.4
K-3.
K-3
Keywords: Amelia-Bedelia -- (Fictitious character) -- Juvenile fiction; Amelia-Bedelia -- (Fictitious character) -- Fiction; Amelia-Bedelia -- (Fictitious character) -- Fiction; Animals -- Juvenile fiction; Zoos -- Juvenile fiction; Animals -- Fiction; Humorous stories; Zoos -- Fiction; Animals -- Fiction; Zoos -- Fiction; Humorous fiction